Stratégies des filières fromagères sous AOP en Europe - Jeanneaux, Philippe (éditions Quae, 2018)
To explain the origin of the differences in milk prices paid to producers, this work provides a framework for analyzing the mechanisms of governance of PDO cheeses, which are organised in localised agri-food systems (SYAL). Six PDO cheeses in Europe are presented: Comté PDO and Cantal PDO in France, Gruyère PDO in Switzerland, AllgÃ¤uer Emmentaler PDO in Germany, Parmigiano-Reggiano PDO in Italy and Queso Manchego PDO in Spain.